2015
DOI: 10.1111/emre.12049
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Knowledge Acquisition on the Relationship Between External Social Capital and Innovativeness

Abstract: In this paper we analyse how external social capital affects innovativeness through knowledge acquisition. Specifically, we test the effect of density, trust and cognitive proximity on the innovativeness of firms and the mediating role of external knowledge acquisition to explain these relationships. We focus our empirical study upon the footwear industry in Spain, using partial least squares to test the proposed hypotheses. The main contribution of this study is to demonstrate how knowledge acquisition leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 125 publications
(227 reference statements)
0
33
0
1
Order By: Relevance
“…For example, Liao and Marsillac (2015) found that firms with AC work to acquire more resources for improvements in product innovation. Firms that can acquire new or valuable resources will develop new lines of products (Parra‐Requena, Ruiz‐Ortega, García‐Villaverde, & Rodrigo‐Alarcón, 2015). However, the success of a green product depends on knowledge inputs from customers as firms take on environmental challenges (Zhao et al, 2018).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…For example, Liao and Marsillac (2015) found that firms with AC work to acquire more resources for improvements in product innovation. Firms that can acquire new or valuable resources will develop new lines of products (Parra‐Requena, Ruiz‐Ortega, García‐Villaverde, & Rodrigo‐Alarcón, 2015). However, the success of a green product depends on knowledge inputs from customers as firms take on environmental challenges (Zhao et al, 2018).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…These entities compile and disseminate knowledge among firms, thereby reducing their search costs (McEvily & Zaheer, 1999). They can also provide information that represents complex and tacit scientific knowledge, which can affect knowledge acquisition (Parra‐Requena, Ruiz‐Ortega & García‐Villaverde, 2015). To measure this, we used one item on the Likert scale previously established in the work by Molina‐Morales and Martínez‐Fernández (2010), which was in turn adapted from McEvily and Zaheer (1999).…”
Section: Methodsmentioning
confidence: 99%
“…The main idea is that density is associated with redundancy of the sources of knowledge. We obtained values for the network density by using the three-item scale of Parra-Requena, Ruiz-Ortega, García-Villaverde, and Rodrigo-Alarcón (2015) that measures the redundancy and the degree of interconnection of the network. To identify the multi-item scale for the construct, we performed an exploratory factor analysis.…”
Section: Methodsmentioning
confidence: 99%